Efeito da radiação micro-ondas sobre a esterificação de ácido oleico catalisado pela lipase NS-40116 livre e ácido sulfúrico - Marangoni, Marluci (2019)
Fatty acid esters are substances commonly found in nature and are used as intermediates in the organic synthesis of many products. They are also obtained by the esterification of fatty acids with alcohols in the presence of catalysts. The esterification reactions can be catalysed by acids, bases or by enzymatic catalysis. An alternative process for esterification is based on the use of microwave irradiation, a technology that is easy to operate, economic in terms of energy, with reduced processing time, extremely fast heating and lower alcohol/oil ratio. The comparison of conventional batch processes with the application of single mode microwave irradiation are aspects proposed in this work. In the context of biotechnological innovation and industrial advances in biocatalytic area, this this study aims to avaluate the esterification of oleic acid/acohol (etanol, 1-Butanol, 1-Hexanol, 1-Octanol), using an chemical (sufuric acid) and enzymatic catalyst (free Lipase NS 40116) against microwave single mode radiation. Esterification reactions were conducted using the following parameters: 1:6 oleic acid / alcohol molar ratio, 1% chemical catalyst, 2% enzymatic catalyst and 10% water, temperature of 45 ° C at different reaction times. Under these conditions, the enzymatic catalyst reaches levels of oleic acid consumption higher than those provided by the use of the chemical catalyst, and after about 2 hours of reaction, 40% of the fatty acid was consumed at the reactions using chemical catalyst, and 10% in those catalyzed by the enzymatic system, suggesting a better performance of the enzymatic catalyst for the reactional conditions investigated without the use of microwaves. The reactions in chemical and enzymatic systems described above were also carried out in microwaves, where it was observed that the catalysts present potential of use against the use of this irradiation. Residual fatty acid results of 93,9% for the enzymatic reactions and 86,8% for sulfuric acid as catalyst, both responses obtained in 120 minutes of reaction, using 20 W of ultrasonic power, at 45 ° C. This study still presents the investigations about cyclic and dynamic modes of irradiation, which indicated that cyclic mode was slightly superior than dynamic mode, probably due to the way the energy is released in these two systems. The use of microwaves suggests advantages over conventional chemical and enzymatic systems, especially when it comes to the reaction time, being distinguished by temperature conditions and mild power.